Cochlear Nerve Hypoplasia: Audiological Characteristics in Children and Adults - Cinar, Betul Cicek; Tahir, Emel; Batuk, Merve Ozbal; Yarali, Mehmet; Sennaroglu, Gonca; Sennaroglu, Levent (Audiology & neurotology, 2019)
Cochlear nerve deficiency is a general term used to describe both cochlear nerve hypoplasia (CNH) and cochlear nerve aplasia. Although these two conditions can have similar results on audiological evaluation, CNH yields more variation in audiological tests. To describe the audiological characteristics of the CNH cases in our series in relation to radiological findings. We reviewed the medical charts, audiological findings, and radiological findings on cases with CNH. We included cases with CNH in one ear or both ears. Out of 90 subjects with CNH, we included a total of 40 individuals (21 women and 19 men; 49 ears) in the current study. We reviewed and analyzed the participants' audiological test results according to the radiological findings. Cases with CNH showed variations according to the cochlear structure. There were 13 normal cochleae, 4 with incomplete partition type I, and 32 with cochlear hypoplasia. The accompanying cochlear apertures also showed variation: 17 were normal, 28 stenotic, and 4 aplastic cochlear apertures. The subjects displayed hearing loss ranging from moderate to profound; furthermore, 4 subjects had no response to sound whatsoever. The degree of hearing loss was not statistically significantly different with regard to the presence or absence of cochlear malformation with CNH (p > 0.005). We observed both sensorineural hearing loss and mixed-type hearing loss among the CNH cases. CNH is the presence of a cochlear nerve that is smaller in diameter than the facial nerve. It can be accompanied with other associated inner ear malformations of different degrees of severity. We observed degrees of hearing loss ranging from moderate to profound.